2(x-2)=3(x+1)
2x-4 = 3x +3
2x-3x = 3 +4
-x= 7
x=-7
2006-12-03 10:16:22
·
answer #1
·
answered by Hera 2
·
0⤊
0⤋
2(x-2) = 3(x+1)
2x - 4 = 3x + 3
-4 - 3 = 3x - 2x
-7 = x
or
x = -7
2006-12-03 12:22:31
·
answer #2
·
answered by vren 1
·
0⤊
0⤋
2(x-2)=3(x+1)
2x-4 = 3x +3
2x-3x = 3 +4
-x= 7
x=-7
2006-12-04 01:16:24
·
answer #3
·
answered by Mikhil M 2
·
0⤊
0⤋
2(x-2)=3(x+1)
2x-4 = 3x +3
2x-3x = 3 +4
-x= 7
x=-7
2006-12-03 10:17:33
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
2(x-2)=3(x+1) distribute 2 & 3
2x-4=3x+3 subtract 2x
-4=x+3 subtract 3
x=-7
2006-12-03 10:16:55
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
2(x-2)=3(x+1)
2x-4 = 3x +3
2x-3x = 3 +4
-x= 7
x=-7
2006-12-04 16:18:32
·
answer #6
·
answered by arpita 5
·
0⤊
0⤋
2(x-2)=3(x+1)
2x-4=3x+3
-4=x+3
-7=x
2006-12-03 10:18:14
·
answer #7
·
answered by sandyclaws08 2
·
0⤊
0⤋
2(x-2)=3(x+1)
2x - 4 = 3x + 3
x = -7
₢
2006-12-03 10:17:59
·
answer #8
·
answered by Luiz S 7
·
0⤊
0⤋
= 2x - 4 = 3x + 3
= 2x-3x = 3 + 4
= -x = 7
= x = -7
-7
2006-12-04 12:27:09
·
answer #9
·
answered by KBH 2
·
0⤊
0⤋
2x-4 = 3x + 3
2x-3x = 3 +4
-x = 7
x = -7
2006-12-03 22:53:24
·
answer #10
·
answered by ns 1
·
0⤊
0⤋